IMPLEMENTASI BAHASA INGGRIS PADA PEMBELAJARAN PENDIDIKAN AGAMA ISLAM SISWA SMAN 04 KOTA MALANG - Fitroh Mushbihin Diwanto; Ika Nuriyanti; Imam Wahyudi Karimullah (Kariman: Jurnal Pendidikan Keislaman, 2022)
English has an important role in various aspects. Including in the aspect of education, where the world of education today must keep up with the times that are full of challenges, one of which is PAI learning with the aim that students can understand religious education as a whole. Because some references currently use a lot of foreign languages, especially English. This study uses descriptive qualitative research methods, namely an activity to understand a phenomenon as an object of research by describing its natural context. The type of this research is field research (Field Research) in this study researchers directly observe events and are directly involved in the field, namely in the process of learning Islamic religious education using English at SMAN 4 Malang. The results of this study indicate that learning PAI using English at SMAN 4 Malang, is able to provide motivation for students to better apply the sacred values ​​of Islam in everyday life. while the implementation of PAI learning using English has succeeded in increasing the ability of students in PAI learning materials. This is evidenced by the critical response of students in linking their religious understanding with the realities of everyday life. In addition, students also show learning outcomes that continue to improve in each learning evaluation, both in daily evaluations or evaluations at the end of the semester